Foreign direct investment and spillover effects on domestic firms - Wenrich, Brian G. (Kansas State University, 2012)
The literature concerning foreign direct investment and the spillover effects on domestic firms has developed significantly over the past two decades. This report examines the historical data on foreign direct investment flows and identifies several different types of spillover effects. Earlier studies identify potential horizontal spillovers but later studies suggest that these spillovers are insignificant. Recently, vertical spillovers, especially through backward linkages, have been identified as occurring in the host country. Studies indicate that this is happening particularly in the manufacturing sector for firms relying on inputs from the services sectors that have higher levels of foreign direct investment.
Keywords: Foreign direct investment; FDI; Economics (0501)